Descolonizar la enseñanza-aprendizaje del derecho hacia una ecología de saberes para formar abogados con enfoque de género y de interculturalidad - Córdova Vinueza, Paúl (2020)
In this work I would like to briefly question the legal foundations of the study of Law and question what are the methodologicaland conceptual orientations of its teaching from a gender and intercultural perspective. The questions that guide this analysisare: what can be the perspectives for discussion to transform your learning from the inclusion of the proposed approaches towards the development of legal pluralism? And what elements would be determining to modify the ways of reasoning and arguing with these approaches and perspectives during the teaching-learning process? The spheres of training respond to symbolic and ritual codes that shape the ways of teaching-learning to think, reason and argue. Based on this consideration, this article proposes that by reinventing those dimensions we will be able to modify their epistemology and the normative and democratic reasons that are built in them to think about learning law at the undergraduate and graduate levels, where we do not ignore that their Intimate truths are born from the very core by the control of power and the power of control of those who create, interpret and apply the legal norm.The propositional vision of this work is designed according to the projections and perspectives of the Constitutional State, in terms of interculturality and plurinationality, which requires another type of legal training and the construction of another normative and state paradigm that overcomes legal monolithism towards the inclusion of pluralism legal.